2023
DOI: 10.1002/cai2.55
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in immunotherapy for lung cancer

Abstract: Lung cancer is the malignant tumor with the highest morbidity and mortality in China, and nonsmall cell lung cancer is a common form of lung cancer. After undergoing chemotherapy and molecular targeted therapy, the treatment of lung cancer has now fully entered the era of immunotherapy. Immunotherapy-based treatment has become one of the standard treatments for lung cancer. Immunotherapy has also gradually moved from the back line to the front line, from advanced to early patients. This article focuses on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The management of advanced lung cancer has evolved into the era of precision medicine ( 26 , 27 ). The selection of an appropriate treatment regimen is determined not merely by the histological subtype but also by the presence of specific driver mutations and the level of PD-L1 expression ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The management of advanced lung cancer has evolved into the era of precision medicine ( 26 , 27 ). The selection of an appropriate treatment regimen is determined not merely by the histological subtype but also by the presence of specific driver mutations and the level of PD-L1 expression ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study on patients with ALK-positive NSCLC treated with crizotinib reported that the absence of PD-L1 expression is linked to prolonged PFS (24). However, divergent findings from another investigation suggest that initial PD-L1 levels do not significantly forecast the success of alectinib therapy in individuals with ALK-positive lung cancer (25).…”
Section: Discussionmentioning
confidence: 99%
“…Both studies showed a significant improvement in OS reaching median OS of 12.3 and 12.9 months for the experimental arm, respectively (10, 15). Although the benefit of the addition of immunotherapy is overall consistent along clinical trials, the modest entity of clinical benefit underlines the complexity of tumor biology and the need for predictive biomarkers and new combination strategies (16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%